Paraprofessionals in Rural development - "Esman, milton J." (Washington, 1983)
The World Bank and other international aid agencies have expanded their commitments in recent years to small-scale agriculture. The sociological and institutional problems of implementing such projects have tended to receive insufficient attention from donors or host governments. This has been especially true of implementation at the field level. There are many oppurtunities to strengthen local institutions and improve the quality and relevance of services by drawing on private enterprise, voluntary organizations and associations of local farmers, as well as improving the performance of government agencies. Many combinations are available to strengthen local action capabilities.
Keywords: Underdeveloped areas-agriculture development